Personalentscheidungen an Musikwissenschaftlichen Lehrstühlen nach 1945 - Malkiewicz, Michael (Muzikološki zbornik, 2013)
Almost all holders of a musicology chair at the universities and academies in Germany could return to their positions after 1945. The reasons why someone could keep his chair in musicology, why some continued their work after a short dismissal by the military government, or why somone was permanently dismissed, are very different.
Keywords: Blessinger, Karl Michael, 1888-1962; kadrovska politika; Korte, Werner, 1906-1982; muzikologija; povojna Nemčija